Unveiling psychological and sociocultural adaptation patterns of international students in Hungary - Gebregergis, Werede Tareke; Csukonyi , Csilla (Journal of International Students, 2025)
The increasing global mobility of students has heightened the need for deeper insights into the psychological and sociocultural adaptation processes in host environments. This study examines the adaptation experiences of 447 international students in Hungary, focusing on the interplay between psychological and sociocultural dimensions of adaptation. Using a cross-sectional design, the study explores how sociodemographic variables, such as gender, age, education level, local friendships, and financial sources, influence adaptation levels. Hierarchical multiple regression analysis reveals that sociocultural adaptation significantly predicts psychological adaptation, underscoring the importance of social integration in fostering overall well-being. The findings suggest that targeted institutional support addressing sociocultural challenges can enhance students' psychological resilience, contributing to their academic and personal success. This research advances the understanding of intercultural adaptation and provides actionable recommendations for policymakers and educational institutions hosting diverse student population.